Text and Context: Exploring Values of Character in "Al-Qiro'ah Al-Rosyidah" Text - Muassomah, Muassomah (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2020)
Al-Qiro'ah al-Rosyidah textbook studied by beginner santri (a term for students admitted to study in Islamic boarding schools) in several Islamic boarding schools in Indonesia is due to its simple vocabulary and easy-to-understand word structure character values that are in line with Islamic values. From the textbook, al-Qiro'ah al-Rosyidah, children and adolescents can learn aspects of language and understand the values and norms implied in each text title. This paper aims to explore the character values containedin the textbook al-Qiro'ah al-Rosyidah. The activities described in the book indicate past activities such as farming, gardening, anchoring, etc. which are different from the present conditions. Therefore,it needs contextualization with value activities in the present. This paper is employing descriptive qualitative research with a literature study approach, namely extracting from a textbook. Data collection was carried out through reading and recording, which were then followed by mapping and classification. Critical discourse analysis techniques are used in analyzing the data in this paper. This paper concludes that the textbook al-Qiro'ah al-Rosyidah contains character values that follow Islamic norms, which are reflected in society's life in the past. These values are in the form of patience, trustworthiness, sincerity, responsibility, help, cooperation, respect for others, etc. This study suggests analyzing the same book as a whole for volumes 1, 2, and 3 so that the values extracted are more diverse according to the varied descriptions of past experiences.